2020
DOI: 10.1080/12298093.2020.1767020
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Tolerance of Novel Papiliotrema Yeast Isolated from Vietnamese Mangosteen

Abstract: Three yeast strains (Hue-1, Hue-8, and Hue-19) with strong heavy metal tolerance were isolated from mangosteen from Hue city, Vietnam. They exhibited identical phenotype and phylogeny. Sequence analysis of the D1/D2 region of the LSU rRNA gene and the internal transcribed spacer (ITS) region demonstrated that the closest relative of these strains is Papiliotrema sp. with 2.12% and 3.55-3.7% divergence in the D1/D2 domain, and ITS domain, respectively. Based on the physiological, biochemical, and molecular data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In previous findings, we showed that P. huenov can tolerate high levels of some heavy metals such as Ni, Pd, and Cd [ 24 ]. In this study, we observed that yeast cells can grow even better at low concentrations of manganese (55 mg/L), or copper (64 mg/L), since biomass (g/L) or cell density (OD) of cultures treated with these metals (12.55–12.8 g/L) was higher than that of controls (12.5 g/L) ( Figure 1(A,B) ; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous findings, we showed that P. huenov can tolerate high levels of some heavy metals such as Ni, Pd, and Cd [ 24 ]. In this study, we observed that yeast cells can grow even better at low concentrations of manganese (55 mg/L), or copper (64 mg/L), since biomass (g/L) or cell density (OD) of cultures treated with these metals (12.55–12.8 g/L) was higher than that of controls (12.5 g/L) ( Figure 1(A,B) ; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Investigations into the effect of manganese and copper on P. huenov were based on cell dynamic development in liquid culture according to the method, previously described [ 24 ] with some modifications. Briefly, P. huenov from the collection at the institute of Biotechnology, Hue University was inoculated into fresh YPD medium agar (1% yeast extract, 1% peptone, 2% glucose, 2% agar).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Sporobolomyces roseus can produce zeatin ( Streletskii et al, 2019 ) and degrade amino acids ( Moore et al, 1968 ). Papiliotrema has been reported to be resistant to heavy metals ( Nguyen et al, 2020 ). These biological functions possibly supply essential nutrients for the growth of cotton boll larvae or aid the host in detoxification processes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell shape and morphology were photographed by light microscopy (CX33, Olympus, Tokyo, Japan). The ability of yeast cells to assimilate carbon and nitrogen sources was evaluated according to a previous study [ 13 ].…”
Section: Methodsmentioning
confidence: 99%